1997
DOI: 10.1002/ir.9504
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Nexus Between College Choice and Persistence

Abstract: The connections between student aid, college choice, and persistence are not always fully understood by institutional researchers and the institutions they serve. This chapter examines and contrasts this nexus for a national sample of students in both the public and the private sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 16 publications
2
51
0
Order By: Relevance
“…Our research draws on previous work regarding working students (Bradley, 2006;Choy & Berker, 2003;Hughes & Mallette, 2003;Pascarella & Terenzini, 2005;Perna, Cooper, & Li, 2006) and the role of financial aid in postsecondary access and success (McDonough & Calderone, 2006;Paulsen & St. John, 1997;St. John, Paulsen, & Starkey, 1996;Stage & Hossler, 2000).…”
Section: Theoretical Perspectives and Previous Researchmentioning
confidence: 98%
“…Our research draws on previous work regarding working students (Bradley, 2006;Choy & Berker, 2003;Hughes & Mallette, 2003;Pascarella & Terenzini, 2005;Perna, Cooper, & Li, 2006) and the role of financial aid in postsecondary access and success (McDonough & Calderone, 2006;Paulsen & St. John, 1997;St. John, Paulsen, & Starkey, 1996;Stage & Hossler, 2000).…”
Section: Theoretical Perspectives and Previous Researchmentioning
confidence: 98%
“…John et al (1996) indicate, the ''reasons why students chose colleges had both a direct and indirect influence on their persistence decisions'' (p. 209). Additionally, both lines of research are applied to enrollment management functions, such as marketing, recruitment and retention (Paulsen and St. John 1997).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…John and Starkey 1995) consider tuition and financial aid separately, since the effects of tuition on enrollment have proven to be different from those of financial aid. In these studies, student enrollment patterns are like those of other commodities in the free market: student enrollment in higher education decreases when the price (tuition in this study) of education is increased, and vice versa (e.g., Heller 1999;Hsing and Chang 1996;Leslie and Brinkman 1987;Paulsen and St. John 1997). Other studies, however, have found small or insignificant effects of tuition on enrollment (e.g., Ghali et al 1977;Wetzel et al 1998).…”
Section: Tuition Elasticity and College Enrollmentmentioning
confidence: 88%